The neural correlates of perceived social support and its relationship to psychological well-being - Lu, Huanhua; Song, Yiying; Wang, Xu; Liu, Jia (Frontiers in Behavioral Neuroscience, 2024)
Perceived social support is considered to play a significant role in promoting individuals' health and well-being, and yet the neural correlates of perceived social support were not fully understood. Herein, we used the Social Provisions Scale to assess individuals' perceived social support, and magnetic resonance imaging was used to measure the gray matter (GM) volume of the whole brain. The voxel-based morphometry analysis of the whole brain revealed that perceived social support was positively correlated with GM volume of the left middle temporal gyrus (MTG).The finding indicated that a person with greater GM volume in the left MTG perceived more social support. More importantly, the left MTG GM volume observed above was also associated with psychological well-being, and the link between the two was mediated by perceived social support. These results revealed the importance of MTG for perceived social support and psychological well-being, and also suggested that perceived social support might explain the relationship between MTG and psychological well-being.